2020
DOI: 10.3390/su12030766
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of the New Generation of Farmers to Participate in Rural Tourism: The Role of Perceived Impacts and Sense of Place

Abstract: This study aims to assess the willingness of the new generation of farmers in China to return to their hometowns for the purpose of contributing to rural tourism. Based on the hierarchy of effects models (HOE) and the social representation theory (SRT), this study utilized an analysis model of perceived rural tourism impacts (P), sense of place (SoP), and willingness to participate (WTP) by the new generation of farmers, where sense of place was deconstructed into the two independent dimensions of place identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 74 publications
(99 reference statements)
1
23
0
1
Order By: Relevance
“…Besides, rural tourism provides a large number of employment opportunities and onthe-job positions for the society and attracts a large number of migrant workers and urban unemployed people to choose to return to their hometowns to start businesses (B. Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, rural tourism provides a large number of employment opportunities and onthe-job positions for the society and attracts a large number of migrant workers and urban unemployed people to choose to return to their hometowns to start businesses (B. Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rural tourism is often positioned as an opportunity for diversification in the face of declining agricultural employment opportunities for rural residents. Li et al (2020) found that farmers in their research in rural China were willing to diversify into rural tourism, however Xue and Kerstetter's (2019) ethnographic study illustrates how transitioning from agriculture to tourism requires a long learning process. In SJHT, Brandth and Haugen (2014) consider how farm tourist hosts embody ideas about rurality, highlighting the gendered aspects of tourist expectations.…”
Section: Nordic and International Research In Rural Tourismmentioning
confidence: 99%
“…Linking the most important components of sustainability [11][12][13][14], agritourism can ensure an innovative and diversifying strategy for farms [15], including recreational and leisure activities for tourists, with many economic and non-economic benefits for farmers, visitors and communities [16]. Not every type of tourism in rural regions, or rural tourism, could be considered agritourism.…”
Section: Literature Reviewmentioning
confidence: 99%